Efficient strategies based on behavioral and electrophysiological methods for epilepsy-related gene screening in the Drosophila model - Liu, Chu-Qiao; Qu, Xiao-Chong; He, Ming-Feng; Liang, De-Hai; Xie, Shi-Ming; Zhang, Xi-Xing; Lin, Yong-Miao; Zhang, Wen-Jun; Wu, Ka-Chun; Qiao, Jing-Da (Frontiers in Molecular Neuroscience, 2023)
Introduction With the advent of trio-based whole-exome sequencing, the identification of epilepsy candidate genes has become easier, resulting in a large number of potential genes that need to be validated in a whole-organism context. However, conducting animal experiments systematically and efficiently remains a challenge due to their laborious and time-consuming nature. This study aims to develop optimized strategies for validating epilepsy candidate genes using the Drosophila model. Methods This study incorporate behavior, morphology, and electrophysiology for genetic manipulation and phenotypic examination. We utilized the Gal4/UAS system in combination with RNAi techniques to generate loss-of-function models. We performed a range of behavioral tests, including two previously unreported seizure phenotypes, to evaluate the seizure behavior of mutant and wild-type flies. We used Gal4/UAS-mGFP flies to observe the morphological alterations in the brain under a confocal microscope. We also implemented patch-clamp recordings, including a novel electrophysiological method for studying synapse function and improved methods for recording action potential currents and spontaneous EPSCs on targeted neurons. Results We applied different techniques or methods mentioned above to investigate four epilepsy-associated genes, namely Tango14, Klp3A, Cac, and Sbf, based on their genotype-phenotype correlation. Our findings showcase the feasibility and efficiency of our screening system for confirming epilepsy candidate genes in the Drosophila model. Discussion This efficient screening system holds the potential to significantly accelerate and optimize the process of identifying epilepsy candidate genes, particularly in conjunction with trio-based whole-exome sequencing.